Public Economy versus Planned Economy. Current Approaches and Problems - Ani Matei (Theoretical and Applied Economics, 2006)
he present paper proposes a review of the current object and problems facing the public economy. For the past decade and a half, public economy has clearly come back in the attention of the research interests of specialists from the Central and Eastern European countries. Among these, the scientific research encompassed by the public economy area interrelates with the international trends. At a closer look, public economy appears to be a science, particularly interdisciplinary, with sociological, political, econometrical or systemic approaches possible to prevail. To continue, the author makes reference to four pillars of the public economy: optimum, welfare, social choice and economic justice that allow different approaches to develop. A science branch, equally theoretical and practical, public economy will stress its connections with the economic and mathematic modeling, systemic analysis or sociological and political research. Still, seve¬ral problems in public economy remain open. These concentrate on the public interest, intervention and decision. Conceptualization, understanding and description of the mechanisms that allow the operationalisation may form the basis for further developments on both theoretical and practical level. A clear distinction in order to justify the title of this article needs to be made. Public economy is not to be confused with planning economy. The state remains but one of the producers and delivery agents of public goods and services.